An easy guide to care for sculpture and antique art collections - Faltermeier, Robert B. (Springer International Publishing, 2014)
This book is a concise guide on how to preserve, protect and analyse cultural heritage in private and public collections. Its focus is on three-dimensional works of art and archaeology crafted from materials like ceramics, glass, stone, metals, wood etc. It briefly explains the most important aspects of handling, display, storage and analysis of such art works and covers the basics of environmental conditions for an art collection. Numerous practical examples from the author's long experience are shown in high-quality colour photographs.